Inovasi Pengembangan Media Pembelajaran Roda Putar berbasis Powerpoint pada Pembelajaran IPAS Kelas 4 SD Negeri Nongkosawit 02 Kota Semarang - Rahmawati, Ika; Suratno, Suratno (Kayon Media, 2024)
Abstract: Lack of interest of students in learning science because there are materials that are not interesting enough, this is caused by the use of media that is not optimal and not varied enough so that in learning students are less active and get bored quickly.This study aims to test the feasibility of the Powerpoint-based Roda Putar learning media, analyze the effectiveness of the Powerpoint-based Roda Putar learning media, and develop the Powerpoint-based Roda Putar learning media.This study uses the Research and Development (RD) method using the ADDIE development model which has five stages: analysis, design, development, implementation, evaluation.Instruments used in collecting data: pretest, posttest and questionnaire.Media expert validity test data and material expert validation were analyzed using descriptive percentage techniques.The results of the expert validator test obtained: (1) the assessment from the media expert validator obtained a percentage of 96.66 percent which indicates an assessment with very feasible criteria, (2) the assessment from the material expert validator obtained a percentage of 92 percent which indicates an assessment with very feasible criteria.Data for student and teacher responses to the media used, including: (1) teacher responses obtained a percentage of 100 percent, (2) small group student responses obtained a percentage of 97.77 percent, (3) large group student responses obtained a percentage of 96.88 percent.The results of the N-gain test showed an increase in pretest and posttest scores of student learning outcomes.Based on the scores obtained, the Roda Putar learning media based on Powerpoint in elementary school grade 4 science learning can be said to be very feasible to use.The implication of this research is that this learning media can be applied by teachers to help students in learning activities so that they do not get bored quickly.Abstrak:Â Kurangnya minat peserta didik pada pembelajaran IPAS karena terdapat matrei yang kurang menarik, hal ini disebabkan karena penggunaan media yang belum optimal serta kurang bervariasi sehingga dalam pembelajaran peserta didik kurang aktif dan cepat bosan. Penelitian ini bertujuan menguji kelayakan media pembelajaran Roda Putar berbasis Powerpoint, menganalisis keefektifan media pembelajaran Roda Putar berbasis Powerpoint, dan mengembangkan media pembelajaran Roda Putar berbasis Powerpoint. Penelitian ini menggunakan metode penelitian dan pengembangan Research and Development (RD) menggunakan model pengembangan ADDIE yang mempunyai lima tahapan: analysis, design, development, implementation, evaluation. Instrument yang digunakan dalam mengumpulkan data: pretest, posttest dan angket. Data uji validitas ahli madia dan validasi ahli materi dianalisis menggunakan teknik deskriptif presentase. Hasil uji validator ahli diperoleh: (1) penilaian dari validator ahli media diperoleh presentase sebesar 96,66Â persen yang menunjukkan penilaian dengan kriteria sangat layak, (2) penilaian dari validator ahli materi diperoleh presentase sebesar 92Â persen yang menunjukkan penilaian dengan kriterian sangat layak. Data untuk respon peserta didik dan guru terhadap media yang digunakan, antara lain: (1) respon guru diperoleh presentase 100 persen, (2) respon peserta didik kelompok kecil diperoleh presentase 97,77 persen, (3) respon peserta didik kelompok besar diperoleh presentase 96,88 persen. Hasil uji N-gain menunjukkan peningkatan nilai pretest dan posttest hasil belajar siswa. Berdasarkan nilai yang diperoleh media pembelajaran Roda Putar berbasis Powerpoint pada pembelajaran IPAS kelas 4 sekolah dasar dapat dikatakan sangat layak untuk digunakan. Implikasi penelitian ini yaitu media pembelajaran ini dapat diterapkan oleh guru untuk membantu peserta didik dalam kegiatan belajar supaya tidak merasa cepat bosan.